PENINGKATAN KEMAMPUAN PEMAHAMAN DAN PEMECAHAN MASALAH MATEMATIS SISWA SEKOLAH MENENGAH ATAS DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION - Maryanti Maryanti; Zulfarazi Zulfarazi (Jurnal Real Riset, 2022)
Up to now the mathematical ability of students is still relatively low, it is characterized from the low mathematics learning outcomes. Low ability students 'mathematical understanding and abilities among students' mathematical problem solving so we need a model of learning that can improve both the mathematical ability. Team Assisted Individualization (TAI) is one type of cooperative learning is expected to increase both these capabilities. This type combines the advantages of cooperative learning and individual learning. This study aims to assess about upgrading the understanding and solving mathematical problems high school students with cooperative learning model Team Assisted Individualization. This study is an experiment that is true experimental research with a quantitative approach. Design research is pretest-posttest control group design. The population in this study were all tenth grade students in the academic year 2013/2014. The sample in this study was 2 classes, X1 (control group) and X2 class (class experiment). Data collection using the test. Data analysis was conducted to gain a score normalized using ANOVA test with the help of SPSS 17.0 software and Microsoft Office Excel 2010. The results showed that: 1) Increased understanding of the mathematical ability of students who obtained using a model of cooperative learning type Team Assisted Individualization better than students which gained overall in terms of conventional learning and student level (high, medium and low), 2) There is no interaction between learning model and student level (high, medium, and low) to increase the capability of understanding, 3) Improving students' mathematical problem solving ability the learning gained by using the cooperative model of Team Assisted Individualization better than students who received conventional learning is reviewed overall and student level (high, medium and low), 4) There is interaction between the learning model and student level (high, medium, and low ) to increase problem-solving ability.Keywords: Understanding Mathematical Ability, Mathematica lProblem Solving Ability, type Cooperative Team Assisted Individualization